Bioaccumulation of Manure-borne antibiotic resistance genes in carrot and its exposure assessment. (December 2021) - Mei, Zhi; Xiang, Leilei; Wang, Fang; Xu, Min; Fu, Yuhao; Wang, Ziquan; Hashsham, Syed A.; Jiang, Xin; Tiedje, James M.
Graphical abstract: Highlights: Manure application increased bioaccumulation of 14 ARGs in carrot tuber by the highest factor of 124. Manure application increased transfer of 13 ARGs from carrot skin to interior by factors of 0.1–11.8. Manure application increased the abundance of ARGs in the carrot leaf. The estimated intake of ARGs for adult and child were 3.2 × 10 7 and 2.7 × 10 7 copies/d by manured carrots, respectively. Peeling may reduce the intake of ARGs in carrots by 28%-91%. Abstract: The effect of manure application on the distribution and accumulation of antibiotic resistance genes (ARGs) in tissue of root vegetables remains unclear, which poses a bottleneck in assessing the health risks from root vegetables due to application of manure. Towards this goal, experiments were conducted in pots to investigate the distribution and bioaccumulation of ARGs in carrot tissues due to application of pig manure. The 144 ARGs targeting nine types of antibiotics were quantified by high throughput qPCR in the soil and plant samples. The rhizosphere was a hot spot for ARGs enrichment in the manured soil. The abundance, diversity, and bioaccumulation factors of ARGs in the phyllosphere were significantly higher than those of carrot root skin and tuber. Manure application increased bioaccumulation of 12 ARGs and 2 MGEs in carrot tuber with 124 the highest factor. The application of manure increased transfer of 10 ARGs and 3 MGEs from carrot skin to inner tuber by factors of 0.1–11.8. The average gene copy number of ARGs of per gram carrot root was about 4.8 × 10 4 and 1.1 × 10 6 in the control and the manured treatment, respectively. Children and adults may co-ingest 2.7 × 10 7 and 3.2 × 10 7 of ARGs copies/d from carrots grown with pig manure, using estimated human intake values. However, peeling may reduce the intake of ARGs by 28–91% and of MGEs by 46–59%. In conclusion, the application of pig manure increased the accumulation of ARGs in the skin of carrots, whereas peeling was an effective strategy to reduce the risk.